(untitled) (Journal of Asian Development Studies, 2024)
Media is a potent source of disseminating news in the present era. So, news regarding violence against Women (VAW) is not an exception. The objective of the present study is to examine how news of VAW is portrayed in the English newspapers of Pakistan. Thepatterns to portrayal of news regarding VAW are based on gendered landscapes through the predictable images of gender identities, which ultimately leads to inequality and biasness against women. The present study investigated the news regarding VAW publishedin the newspapers. VAW is also generally known as domestic violence. The researchers conducted a discourse analysis of five English newspapers and collected 510 newsreportsregarding VAW published during 2017 and 2018. In order to make the findings objective and replicable, the researchers used Critical Stylistics(LesleyJeffries, 2010a) and Sketch Engine, a computer-based corpus software. Findings suggested that the ethical guidelines proposedby various journalist organization were flagrantly violated. These violations involve revealing the victims’ identity i.e.,age, location, and even slantingly holding the victims responsible for the violence. The researchers discovered that these unethical practices may result in inappropriate and stereotypical narrativesabout women.Therefore, it becomes necessary for the media to uphold the ethical considerations to assure the appropriate understanding of VAW and its severity